P Pengaruh Pergantian Antar Waktu terhadap Refresentasi Konstitusi di Parlemen: Pergantian Antar Waktu - mei, mei Hastuti; Mei Hastuti (Program Studi Hukum Tata Negara dan diterbitkan oleh Program Studi Hukum Tata Negara dan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Sunan Drajat Lamongan, 2024)
This study examines the influence of inter-time replacement on constituent representation in parliament with the research method used, namely normative research. This study uses secondary and primary data, the secondary data referred to here is in the form of references or libraries, including literature books, journals, articles, and legislation. Primary legal materials are laws and regulations, official documents, court decisions, and the constitution. The results of the study concluded that PAW can reduce public trust in legislative institutions, PAW has a major influence on political parties to determine who has the right to occupy parliamentary seats and PAW can influence legislative accountability. Keywords: legislature, parliament, constituents, inter-time change